Components of the metabolic syndrome among a sample of overweight and obese Costa Rican schoolchildren - Holst Schumacher, Ileana (2009)
Background. The term “pediatric metabolic syndrome” includes a cluster of cardiovascular risk factors such as insulin resistance, dyslipidemia (including increased triglycerides and decreased HDL cholesterol), hypertension, and obesity in children. No studies have been performed on this syndrome in a pediatric population in Costa Rica. Objective. To establish the prevalence of metabolic syndrome and its components in 8- to 10-year old prepuberal overweight and obese schoolchildren. Methods. This cross-sectional survey was conducted in 214 overweight and obese boys and girls, aged 8 to 10 years, who were selected from six urban schools from San José, Costa Rica. Anthropometric measurements and determinations of blood glucose, insulin, triglycerides, total cholesterol, HDL cholesterol, and high-sensitivity C-reactive protein (hs-CRP) were performed. The homeostasis model assessment of insulin resistance (HOMAIR) index and the Castelli index were calculated to assess insulin resistance and cardiovascular risk, respectively. Social and lifestyle variables were obtained through validated questionnaires. Results. A total of 110 boys and 104 girls participated in this study; 37.9% of them were overweight and 62.1% were obese. Compared with boys, girls were more sedentary and had higher insulin levels (16.05 ± 10.45 μIU/ mL vs. 12.72 ± 7.63 μIU/mL, p = .008), body fat (36.5% vs. 30.9%, p < .001), and HOMA-IR indexes (3.5 ± 2.4 vs. 2.8 ± 1.7, p = .014) but lower HDL cholesterol (0.99 ± 0.23 mmol/L vs. 1.08 ± 0.27 mmol/L, p = .009). Obese children had significantly higher mean serum concentrations of insulin, hs-CRP, and triglycerides and higher insulin resistance (estimated by HOMA-IR) than overweight children, but lower mean serum levels of HDL cholesterol. The prevalence of metabolic syndrome in the study population was 5.6%. Other risk factors for developing cardiovascular disease and type 2 diabetes had high prevalence rates among the children: sedentarism (40.6%), family history of type 2 diabetes (73.3%), high LDL cholesterol levels (≥ 2.84 mmol/L) (57.0%), hyperinsulinemia (> 10.5 μIU/mL) (59.8%), insulin resistance (estimated by HOMA-IR ≥ 2.4) (55.1%), and total cholesterol (> 4.39 mmol/L) (60.7%). Children with metabolic syndrome had significantly higher body mass indexes, glucose levels, and triglyceride levels and lower HDL cholesterol levels than children without metabolic syndrome. Insulin had a very strong positive correlation with HOMA-IR values (r = 0.982), and hs-CRP had a mild positive correlation with body mass index (r = 0.296) and body fat (r = 0.320). Conclusions. This study reported a prevalence of 5.6% of metabolic syndrome among a sample of Costa Rican overweight and obese prepuberal children. Lifestyle interventions focusing on weight reduction and increasing physical activities should be promoted by education and health authorities in order to avoid the early development and onset of type 2 diabetes and atherosclerosis in childhood